National clinical practice guidelines for allergen immunotherapy: An international assessment applying AGREE-II - Larenas-Linnemann de Martínez, Désirée E.S.; Pfaar, Oliver (Allergy, 2018)
Background: Since 1988, numerous allergen immunotherapy guidelines (AIT-GLs) have been developed by national and international organizations to guide physicians in AIT. Even so, AIT is still severely underused. Objective To evaluate AIT-GLs with AGREE-II, developed in 2010 by McMaster University methodologists to comprehensively evaluate GL quality. Methods Allergist, from different continents, knowledgeable in AIT and AGREE-II trained were selected into the project team. The project received methodologists’ guidance. AIT-GLs in any language were sought from 1980 to 2016; AIT-GLs were AGREE II-evaluated by at least 2 team members, independently; discrepancies were resolved in a second round, by team discussion or methodologists’ consulting. Results We found 31 AIT-GLs (15 post-2010), ranging from local consensus reports to international position papers (EAACI, AAAAI-ACAAI, WAO). Pre-2010 GLs scored 1.6-4.6 (23%-67%) and post-2010 GLs scored 2.1-6 (30%-86%), on a 7-point Likert scale. The highest scores went to: German-Austrian-Swiss (6.0), Mexican (5.1), and the AAAAI/ACAAI AIT-GL (4.7). These were also the only 3 GLs that received “yes” of both evaluators to the item: “I would recommend this GL for use.” The domains of “Stakeholder involvement” and “Rigor of Development” only scored 3/7, and “Applicability” scored the lowest. Strikingly, newer GLs only scored clearly better in “Editorial independence” and “Global evaluation.” Conclusions: In AIT-GLs, there is still a lot of room for improvement, especially in domains crucial for the dissemination. For some GLs, the “Scientific rigor” domain flawed. When resources are limited, transculturizing a high-quality GL might be preferable over developing a GL from zero. Our study and AGREE-II could help to select the best candidate. Clinical Implications We here evaluate allergen immunotherapy guideline (AIT-GL) quality. Only high-quality AIT-GLs should be consulted for AIT management decisions. In low-resource settings, transculturization of these is preferred over developing low-quality guidelines.
First published: 21 September 2017
Gesehen am 27.09.2018